LEAF ANATOMY CHARACTERS IN THE TAXONOMY OF PHALAENOPSIS AND ITS RELATIVES IN INDONESIA - Nina Dwi Yulia; Juliarni Juliarni (Floribunda, 2006)
Nina Dwi Yulia & Juliarni. 2006. Leaf Anatomy Characters in The Taxonomy of Phalaenopsis and its Relatives in Indonesia. Floribunda 3(2): 52-56.- Stomatal size, epiderm cell shape and structure and leaf thickness in Paraphalaenopsis, Doritis and Phalaenopsis are different. However, those characters are similar in Phalaenopsis and Kingidium.  Cladistic analysis of Phalaenopsis and its relatives using Hennig86 produced a cladogram with 10 steps and ended with the 3 closest genera, Doritis, Kingidium and Phalaenopsis.